2014
DOI: 10.1007/s10753-014-0005-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Humic Acid on Focal Cerebral Ischemia Injury: an Experimental Study in Rats

Abstract: Stroke is still a major cause of death and permanent neurological disability. As humic acids are well-known antioxidant molecules, the purpose of this study was to investigate the potential neuroprotective effects of humic acid in a focal cerebral ischemia model. Twenty-four rats were divided equally into three groups. A middle cerebral artery occlusion model was performed in this study where control (group II) and humic acid (group III) were administered intraperitoneally following an ischemic experimental pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…As the toxic final product of lipid peroxidation, MDA is a sensitive marker of oxidative stress and is responsible for cytotoxic effects and neuronal death ( 32 ). An efficient antioxidant defense system involving endogenous antioxidant enzymes, such as SOD, GSH-Px and CAT ( 33 ) plays an important role in the maintenance of low concentrations of oxidants and redox homeostasis in tissue through the scavenging of oxidants, preventing deleterious ROS generation ( 34 ). In the present study, we demonstrated that pre-treatment with Mat for 7 consecutive days significantly increased SOD, GSH-Px, CAT and activity, and T-AOC, and decreased MDA levels in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…As the toxic final product of lipid peroxidation, MDA is a sensitive marker of oxidative stress and is responsible for cytotoxic effects and neuronal death ( 32 ). An efficient antioxidant defense system involving endogenous antioxidant enzymes, such as SOD, GSH-Px and CAT ( 33 ) plays an important role in the maintenance of low concentrations of oxidants and redox homeostasis in tissue through the scavenging of oxidants, preventing deleterious ROS generation ( 34 ). In the present study, we demonstrated that pre-treatment with Mat for 7 consecutive days significantly increased SOD, GSH-Px, CAT and activity, and T-AOC, and decreased MDA levels in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The estimation of sample size was dependent on the standard deviation as in a published study by Ozkan et al . Sample size was at least seven gerbils per group with an alpha error of 0.05 and a power of >80%, and the sample size was calculated with power calculator (UCLA Department of Statistics, http://www.stat.ubc.ca/~rollin/stats/ssize).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the autophagic processes have been increasingly shown to have protective functions against ageing and many diseases including cancers, neurodegenerative diseases ( Fig. 2; Cuervo, 2004;Ferrari et al, 2011;Hippert et al, 2006;Mizushima et al, 2008;Ozkan et al, 2015;Rubinsztein et al, 2011;Salminen & Kaarniranta, 2009a;Selvakumaran et al, 2013;Trocoli & Djavaheri-Mergny, 2011;Zhang et al, 2012). Autophagic lysosomal digestion is triggered by many environmental stressors including caloric restriction (CR), hypoxia, ROS, exercise, many toxins and phytochemicals, and sunlight and vitamin D mediated via the vitamin D receptor -VDR (Chatterjee etal., 2014;Delmas et al, 2011;Ferrari et al, 2011;Mestre & Columbo, 2013;Moore et al, 2008;Wu & Sun, 2011;Zhang et al, 2012).…”
Section: Autophagy Anti-ageing and Possible Hormetic-type Effectsmentioning
confidence: 99%